IMPACT DE DÉCALAGE D’ORIGINE SUR LES TOLÉRANCES DE FABRICATION - Rahou, Mohamed; Sebaa, Fethi; Cheikh, Abdelmadjid (European Scientific Journal, ESJ, 2014)
The calculation of tolerances has a significant effect on the function of a product and especially the cost of production. The synthesis of the tolerances is a procedure that is used to distribute the dimension tolerance condition tolerances on all components of the chain dimensions. Dispersions allow us to check before making study projects and optimize manufacturing dimensions by machining simulation The objective of this work is to study the influence of the cutting tool path on the manufacturing tolerances. To achieve this, an experimental study focused on two stages. In the first stage the movement is made in two sequences by da against the second stage is done in one step.